Surface modification of Ti40Cu40Zr11Fe3Sn3Ag3 amorphous alloy for enhanced biocompatibility in implant applications - Kirti Tiwari; Andreu Blanquer; Cristina Pavan; Maura Tomatis; Nora Fernandez Navas; Federico Scaglione; Gianluca Fiore; Francesco Turci; Carme Nogués; Paola Rizzi (Journal of Materials Research and Technology, 2024)
This study focuses on the design of a new Ti based multicomponent amorphous alloy for the development of biocompatible implant materials with enhanced hemocompatibility and cytocompatibility. While this class of amorphous alloys has shown its potential for biomedical implant applications, there are major concerns due to the presence of elements such as copper which can lead to cytotoxicity in the human body during long term implantation. Nevertheless, copper is indispensable in the development of an amorphous alloy. Thus, the objective of this work is to selectively remove copper from the surface of the Ti40Cu40Zr11Fe3Sn3Ag3 (at%) amorphous alloy using the dealloying technique and produce a patterned protective passivated surface rich in Ti and Zr oxides. Nitric acid (HNO3) has been found to be effective in depleting copper from the sample surface. Optimization of treatment parameters such as temperature (70 °C and room temperature) yielded drastic differences in the morphology of the samples studied using Field-Emission Scanning Electron Microscopy. The treated sample surface demonstrated good hemocompatibility and cytocompatibility with primary human osteoblast cells (HOb) and human osteosarcoma cell line (Saos-2). Additionally, the treated samples showed higher ability to produce reactive oxygen species with respect to pristine samples, which could be convenient for preserving the implant from bacterial contamination. These findings contribute to the advancement of producing copper-depleted nanostructured Ti based amorphous alloys for biomedical implant applications.